Tempos distópicos? Dimensão política da educação nos projetos sociais de Fahrenheit 451 e Admirável Mundo Novo - Rosa, Nilber Martins (2017)
In our work, we intend to point out critics, referring to the educational aspects, based on Brave New World (1932), by Aldous Huxley and Fahrenheit 451 (1953), by Ray Bradbury, that have the intensity to question educational policies present in our time, that is, modernity. Dystopian literature, presented in the works, has a great critical force, and we will appropriate this presupposition to analyze questions essential to the educational process. Therefore, we seek to establish a dialogue with the philosopher Theodor Adorno and his writings Education and Emancipation and Aldous Huxley and utopia, in order to glimpse the real objectives that should be sought in an educational process. In the search to identify these fundamentals, we carried out a theoretical bibliographical research, in which we dedicate ourselves to the presentation of the plot from two works. Subsequently, our intentionality will converge to the detailed study of the educational aspects presented, seeking to perceive the theoretical frameworks criticized by the literary authors. In the third and final chapter, we will establish, by Adorno's vision, some assumptions, for the development of education facing enlightenment/autonomy. We believe that the critical provocations contained in the works Brave New World and Fahrenheit 451 can contribute to the development and, above all, can stimulate a reflection on the educational routes that we are treading in our country.